1974
DOI: 10.2136/sssaj1974.03615995003800010040x
|View full text |Cite
|
Sign up to set email alerts
|

Field Measurement of Evaporation from Soil Shrinkage Cracks

Abstract: Weighing lysimetry was used to determine evaporative fluxes from a natural shrinkage crack and from an artificially induced soil shrinkage crack. Evaporation from the soil surface, except at the crack opening, was prevented by covering the lysimeter with plastic film. Evaporation rates from the natural and induced crack averaged about 0.6 mm/day computed on the basis of the surface area of the lysimeter. The horizontal soil water flux in the liquid phase to the crack wall was quite low, indicating that most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…Furthermore, this work expands on previous studies that have explored evaporation from cracked soil (Adams and Hanks, 1964;Adams et al, 1969;Selim and Kirkham, 1970;Ritchie and Adams, 1974) and provides comprehensive subsurface observations and a theoretical framework to explain why the presence of desiccation cracks increases the total evaporation from clay sediment and consequent sediment salinization. Combining observations on (1) rapid and deep water infiltration through desiccation cracks in clay sediments (Baram et al, 2012a), (2) increased sediment salinization with depth under the waste sources and their margins, (3) isotopic signature (δ 2 H and δ 18 O) of the vadose zone pore water that indicates subsurface evaporation, (4) transport of sorptive contaminants to deep sections of the vadose zone (Arnon et al, 2008), and (5) extensive aeration of the vadose zone, which supports nitrification under anaerobic water sources with a very high organic load (Baram et al, 2012b;Sher et al, 2012), has led to the development of a conceptual model, hereafter termed as desiccation-crack-induced salinization (DCIS) (Fig.…”
mentioning
confidence: 68%
“…Furthermore, this work expands on previous studies that have explored evaporation from cracked soil (Adams and Hanks, 1964;Adams et al, 1969;Selim and Kirkham, 1970;Ritchie and Adams, 1974) and provides comprehensive subsurface observations and a theoretical framework to explain why the presence of desiccation cracks increases the total evaporation from clay sediment and consequent sediment salinization. Combining observations on (1) rapid and deep water infiltration through desiccation cracks in clay sediments (Baram et al, 2012a), (2) increased sediment salinization with depth under the waste sources and their margins, (3) isotopic signature (δ 2 H and δ 18 O) of the vadose zone pore water that indicates subsurface evaporation, (4) transport of sorptive contaminants to deep sections of the vadose zone (Arnon et al, 2008), and (5) extensive aeration of the vadose zone, which supports nitrification under anaerobic water sources with a very high organic load (Baram et al, 2012b;Sher et al, 2012), has led to the development of a conceptual model, hereafter termed as desiccation-crack-induced salinization (DCIS) (Fig.…”
mentioning
confidence: 68%
“…Using a precision Iysimeter, Ritchie and Adams (1974) presented data to compare the relative evaporation, E / ET o (grass reference potential ET) for bare soil with a 60-cm-deep crack and for the same area with the bare soil (but not the crack) covered. The experiment was conducted at the ce wp is the volumetric water content of the soil at wilting point.…”
Section: Bare Soil Evaporation Without Stubble or Mulchmentioning
confidence: 99%
“…There fore, most of the evaporation was coming from the crack. Ritchie and Adams (1974) suggested that near the end of the sorghum growing season the evaporation from the cracks could be 0.5 mm! day.…”
Section: Bare Soil Evaporation Without Stubble or Mulchmentioning
confidence: 99%
“…Water in dry Vertisols moves through preferential flow to deeper layers and significantly reduces surface runoff. In contrast to the infiltration process, open cracks may enhance evaporative flux as direct evaporation might be possible through deep soil layers 20,32 . Conventional tillage practice disintegrates larger soil clods into finer pieces and fills wider-cracks with loose soil, which may result into early closing of cracks.…”
Section: Soil Water Balancementioning
confidence: 99%
“…In fact, undisturbed cracks under no-till practices are beneficial to redistribute the water in deeper soil layers 19 . Wider and deeper cracks partially expose sub-surface layers to atmosphere and increases evaporation 20,21 . A significant portion of green water stored in vadose zone may be lost from the system which subsequently could affect the crop water availability and groundwater recharge negatively in the following rainy season.…”
Section: Introductionmentioning
confidence: 99%